Message from the Rector - Hamali, Jamil (UiTM Sarawak, 2018)
This year 2018 is a year of change as we witness tremendous changes in the Federal Government after Pilihan Raya Umum (PRU) 14. These changes call for a need to adjust to new policies. I would like to thank UiTM Sarawak staff for exercising their right to vote. As a Federal Agency, UiTM Sarawak will collaborate with the new government to forge ahead for a New Malaysia. At the same time, we will continue to foster close ties and cooperation with the State Government which has been very supportive of UiTM Sarawak.